The Relationship Between Toluene Intake with LDL and MDA Levels in Car Painting Workshop Workers - Herman Bagus Dwicahyo; Abdul Rohim Tualeka; Tofan Agung Eka Prasetya; Abdullah Al Mamun; Nur Anisah Rahmawati (Public Health of Indonesia, 2026)
Background: Oxidative stress can cause health problems for workers and affect productivity for workers. Low-Density Lipoprotein (LDL) and Malondialdehyde (MDA) levels a biomarkers for systemic oxidative stress. Car painting and body repair businesses play a crucial role in preventing corrosion and damage from crashes by employing a variety of processes. The worker in the stage poses the highest risk of exposure to the chemical substance known as toluene. Objective: The purpose of this study is to investigate the relationship of toluene intake with Low-Density Lipoprotein (LDL) and Malondialdehyde (MDA) levels. Methods: This study employed an observational research design with a cross-sectional method. All 30 car painting workshop workers in sanding, caulking, painting, polishing, and finishing are included in this research. Workers were measured for exposure to Toluene and Low-Density Lipoprotein (LDL) and Malondialdehyde (MDA) levels. Data were analyzed descriptively and statistically. Results: Almost half of the total workers are adults. More than half of the total workers have a working period of 8 hours/day, have a working period of up to 10 years, and BMI in the normal category. Only a small number of workers do not smoke. Toluene exposure that enters the body of workers has more than the reference dose and is found in more than half of the total workers. Most workers have optimal LDL. More than half of the total workers have low MDA. The results of the Toluene exposure test with LDL obtained p = 0.098, and toluene exposure with MDA (malondialdehyde) obtained p = 0.045. Conclusion: There is a relationship between Toluene and MDA, but not with LDL. This indicates the need for efforts to anticipate Toluene exposure in companies to prevent oxidative stress, preceded by an increase in MDA. Keywords: Toluene; Low-Density Lipoprotein; Malondialdehyde; Car painting; Worker